2021
DOI: 10.1038/s41372-021-01125-3
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and safety of repeat dexamethasone for bronchopulmonary dysplasia

Abstract: Objective: To describe effectiveness of repeat dexamethasone for bronchopulmonary dysplasia (BPD) and to evaluate adverse effects on growth. Study design: Retrospective study of infants treated with 1 or 2 courses of dexamethasone for BPD. Effectiveness was defined as successful step-down in respiratory support by end of treatment. Adverse effects on growth were analyzed and compared to untreated controls. Results: A total of 132 dexamethason… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Furthermore, a longer term study has identified a greater reduction in lung function in school aged children associated with larger cumulative doses of postnatal dexamethasone in infants born at less than 29 weeks of gestation [19]. It has recently been reported that 19 to 39% of PNS-treated infants received repeated courses of PNS with varying effectiveness in facilitating a step down of respiratory support in 38-93% of infants [20][21][22]. A strength of this study is the use of a national dataset that allowed us to create an overview of premature infants born in the UK between 2014 and 2018.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a longer term study has identified a greater reduction in lung function in school aged children associated with larger cumulative doses of postnatal dexamethasone in infants born at less than 29 weeks of gestation [19]. It has recently been reported that 19 to 39% of PNS-treated infants received repeated courses of PNS with varying effectiveness in facilitating a step down of respiratory support in 38-93% of infants [20][21][22]. A strength of this study is the use of a national dataset that allowed us to create an overview of premature infants born in the UK between 2014 and 2018.…”
Section: Discussionmentioning
confidence: 99%
“…Preterm infants who remain on a ventilator for more than 2 weeks are considered to have a high risk of developing BPD. [ 47 ] In addition to pulmonary problems in the long term, neurodevelopmental problems, CP, cognitive deficits, and deafness can be seen in children with BPD. It is known that CP and motor abnormalities were seen when dexamethasone is used, especially in preterm infants with a low risk of BPD.…”
Section: What Should Be the Timing Of Steroid Administration? When Sh...mentioning
confidence: 99%
“…It has been reported that the second-cure steroid requirement is higher in babies with SGA and twins. [ 47 ] It was found that the success of extubation decreased in babies who received the second cure of dexamethasone treatment; while an extubation success could be achieved in the first cure around 50%, it was found that the extubation success rate in the second cure was around 35%. [ 47 ] It has been reported that there is no difference between the increase in weight, height, and head circumference when babies who receive a single cure and those who receive two cures are compared according to their anthropometric measurements at discharge.…”
Section: Second-cure Steroid Usementioning
confidence: 99%
See 2 more Smart Citations